2013
DOI: 10.3748/wjg.v19.i11.1778
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between dietary factors,CagA-positiveHelicobacter pyloriinfection, andRUNX3promoter hypermethylation in gastric cancer tissue

Abstract: These results suggest that the CagA status of H. pylori infection may be a modifier of dietary effects on RUNX3 methylation in gastric cancer tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Similar, but inverse, effects occur when zinc is limited (39) . Dietary habits such as high consumption of salt, proteins or nitrite have also been linked to the pathogenicity of H. pylori (40) . Furthermore, conditions in the stomach environment, such as altered pH, could facilitate colonization of the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Similar, but inverse, effects occur when zinc is limited (39) . Dietary habits such as high consumption of salt, proteins or nitrite have also been linked to the pathogenicity of H. pylori (40) . Furthermore, conditions in the stomach environment, such as altered pH, could facilitate colonization of the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies among different geographical populations have shown that there might be association between infection with H pylori and Gastric cancer development (Thomazini et al, 2006;Zhang et al, 2013). Thomazini and colleagues (2006), for instances, observed that 95% of Brazilian patients with Gastric cancer had infection with H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cagA gene of H pylori is revealed to be involved in pathogenesis of Gastric cancer (Graham and Yamaoka, 1998;Zhang et al, 2013). In addition, cagA and the vacuolating cytotoxin (vacA) genotypes are proposed to serve as predictors for progression of gastric lesions (Gonzalez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A body of evidence suggests that Runx3 may function as a tumor suppressor in various cancer types (22)(23)(24). Some studies have indicated that inactivation of Runx3 protein by various chemical modifications may contribute to tumor pathogenesis, initiation and progression in specific microenvironmental contexts.…”
Section: Discussionmentioning
confidence: 99%